KRISIS: KRISTEN TERHADAP ISU ISIS - Suciati Dr (Komunikator, 2015)
Islamic State of Iraq and Syria (ISIS) declared themselves as an Islamic community. Rebel movement of ISIS is based on the goals of what is right and what is wrong of what ISIS believe. They have been done give bad impact to the way people see Islam itself. It is getting worse by the intense ISIS news covered by mass media. Christians, known as the most people who get the most disadvantage caused by ISIS. This is why it is interesting to know deeper of what the Christians in another place feel of this issue. The research is to see how the Christians get the conclusion of how mass media covering the ISIS news.The research is going to be a descriptive with an interactive qualitative analyzing research, to discuss in a forum as a place for nine Christians as member of Gereja Baptis Indonesia Saman, district of Sewon, Bantul Region, Yogyakarta. The goal is to know the affection, cognition, and conation, to know how Christians behave in daily life based on massive mass media reported about ISIS and to know the damage of harming the name of Islam because of the conflicts that often  Keywords: ISIS, Christian, mass media news, the trilogy of mind